Penggunaan Ayat-ayat dalam al-Qur’an Sebagai Media Pengobatan - Sormin, Nurhabibah; Hasiah, Hasiah; Enghariano, Desri Ari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The problem in this study is the verses of the Koran used and the process of using them as a medicinal medium in Padangsidimpuan City. The type of research in this writing is field research using a qualitative approach, the primary data sources in this study are several Ustadz who perform treatment with verses of the Koran. Secondary data sources are in the form of books, journals and documentation related to this research. Data collection techniques through observation, interviews and documentation. The research type data analysis technique is descriptive. The results of the study showed that the treatment carried out by Ustadz in Padangsidimpuan City used the verses of the Koran. Some Ustadz use the same verses in the treatment process. some other Ustadz use different verses. Furthermore, the treatment process carried out by several Ustadz in Padangsidimpuan City was also carried out in different ways. An example of the process is first the Ustadz is already in a state of ablution, then asks the patient's complaints, after that starts reciting verses from the Koran in treatment, and provides water media and other herbal media.